Low birth weight and prenatal care in Colombia: A cross-sectional study (2015)
Background: Low birth weight (LBW) is one of the most important factors affecting child morbidity and mortality worldwide; approximately one third of neonatal deaths are attributable to it. Most research and public health policy on LBW arise from developed nations, despite that most cases (96.5%) take place in developing countries. The specific features of prenatal care that prevent LBW in developing countries are unclear. This study aims to identify the characteristics of prenatal care associated with LBW in a developing country as Colombia. Methods: Observational cross-sectional study using data from the Colombian Demographic and Health Survey 2010. A total of 10,692 children were included. Descriptive statistics were calculated, followed by bivariate regressions of LBW with all other study variables. Finally, stepwise logistic binomial regression analyses were done. Results: A LBW prevalence of 8.7% was found. Quality of prenatal care (95%CI: 0.33, 0.92; OR=0.55), number of prenatal visits (95%CI: 0.92, 0.93; OR=0.92), and first prenatal visits during pregnancy (95%CI: 1.02, 1.07; OR=1.08) were associated with LBW even after controlling for all the studied variables. The health care provider conducting prenatal checkup, and insurance coverage, were not associated with LBW. Conclusion: This research provides information on the characteristics of prenatal care (quality, number of visits, and gestational age at first prenatal visit) which may strengthen LBW prevention in Colombia and possibly in countries with similar socioeconomic characteristics. © 2015 Pinzón-Rondón et al.